Cycling in the post-socialist city: On travelling by bicycle in Sofia, Bulgaria. (July 2016) - Barnfield, Andrew; Plyushteva, Anna
There are many ways of moving through a city. Cycling is one which has received considerable attention from urban scholars. Yet it has remained largely neglected within the burgeoning literature on the post-socialist urbanisms of Central and Eastern Europe. This paper uses a case study from Sofia, Bulgaria to address this gap in urban research. By exploring the practices and affordances of cycling, we offer a discussion of everyday mobility, public life and urban space in post-socialist Sofia. This case study incorporates ethnography and in-depth interviews with regular cyclists. Through a discussion of bicycling spaces and practices, this paper complicates the notion of post-socialist cities as places defined by the decline of public sensibilities.